Outpatient visit trends for internal medicine ambulatory care sensitive conditions after the COVID-19 pandemic: a time-series analysis - Ciara Pendrith; Dhruv Nayyar; Cherry Chu; Tara O'Brien; Owen D. Lyons; Payal Agarwal; Danielle Martin; R. Sacha Bhatia; Geetha Mukerji (BMC, 2022)
Abstract Background The COVID-19 pandemic led to a dramatic shift in the delivery of outpatient medicine with reduced in-person visits and a transition to predominantly virtual visits. We sought to understand trends in visit patterns for ambulatory care sensitive conditions (ACSCs) commonly seen in internal medicine clinics. Methods We included adult outpatients seen for an ACSC between March 15th, 2017 and March 14th, 2021 at a single-centre in Ontario, Canada. Monthly visits were assessed by visit type (new consultation, follow-up), diagnosis, and clinic. Time series analyses compared visit volumes pre- and post-pandemic. Proportion of virtual visits were compared before and during the pandemic. Patient and visit factors were compared between in-person and virtual visits. Results 8274 patients with 34,021 visits were included. Monthly visits increased by 15% during the pandemic (p <  0.0001). New consultations decreased by 10% (p = 0.0053) but follow-up visits increased by 21% (p <  0.0001). Monthly heart failure visits increased by 43% (p <  0.0001) whereas atrial fibrillation visits decreased. Pre- pandemic, < 1% of visits were virtual compared to 82% during the pandemic (p <  0.0001). Less than half of heart failure visits were virtual whereas > 95% of diabetes visits were virtual. Conclusions We found a significant increase in overall visits to internal medicine clinics driven by increased volumes of follow-up visits, which more than offset decreased new consultations. There was variability in visit trends and uptake of virtual care by visit diagnosis, which may indicate challenges with delivery of virtual care for certain conditions.